Endoscopic features of cytomegalovirus disease of the upper gastrointestinal tract between transplant and non-transplant patients - Yuri Kim; Do Hoon Kim; Myeongsook Seo; Hee Kyong Na; Kee Wook Jung; Ji Yong Ahn; Jeong Hoon Lee; Kee Don Choi; Ho June Song; Gin Hyug Lee; Hwoon-Yong Jung (The Korean Journal of Internal Medicine)
Background/Aims Cytomegalovirus (CMV) disease in the upper gastrointestinal (UGI) tract frequently occurs in immunocompromised patients. However, data regarding UGI CMV disease in non-transplant patients compared with those in transplant recipients are limited. Therefore, we compared the clinical characteristics, endoscopic findings, and outcomes of UGI CMV disease in non-transplant patients with those in transplant recipients. Methods We reviewed the medical records of patients diagnosed with UGI CMV disease between May 1999 and January 2022. UGI CMV disease was defined as symptoms or signs of gastrointestinal disease with typical findings of CMV inclusion body and positive immunochemistry stain or CMV polymerase chain reaction from the endoscopic biopsy specimen. Results Among the 219 eligible patients, 132 (60.3%) were transplant patients. Age, male sex, and Charlson Comorbidity Index were significantly higher in the non-transplant group than in the transplant group. The most common symptoms were pain and odynophagia (43.8%). Transplant recipients more frequently experienced UGI CMV disease in the stomach than non-transplant patients, typically presenting as erosions or mucosal hyperemia. However, non-transplant patients more commonly experienced UGI CMV disease in the esophagus than transplant recipients, typically presenting as ulcers. The transplant group had a significantly higher clinical response than the non-transplant group. Conclusions UGI CMV disease in transplant patients can be present in the stomach in various forms, including ulcers or erosions. In transplant patients suspected of UGI CMV disease, conducting an esophagogastroduodenoscopy with tissue biopsy in any area where even the slightest mucosal abnormality is observed is essential to facilitate a prompt diagnosis.